Peran Strategi Pemasaran Inovatif, Kualitas Pelayanan dan Fasilitas Pelabuhan Terhadap Peningkatan Wisatawan Di Pelabuhan Benoa, Bali Dengan Kepuasan Wisatawan Sebagai Variabel Mediasi - Cahyani, Ni Putu Anggita Vira; Maheswari, Anak Agung Istri Agung; Tirtayani, I Gusti Ayu; Wisudawati, Ni Nyoman Sri (Masyarakat Ekonomi Syariah Bogor, 2025)
Maritime tourism in Bali continues to develop and has become one of the key sectors supporting the regional economy. Benoa Port plays a strategic role as a gateway for both international and domestic cruise tourists, especially after the development of the Bali Maritime Tourism Hub (BMTH). This study aims to examine the influence of innovative marketing strategies, service quality, and port facilities on the increase of tourists, with tourist satisfaction as a mediating variable. The research applies a quantitative approach with data collected through questionnaires. The population consists of tourists visiting Benoa Port, while the sample is determined using an accidental sampling technique with a total of 108 respondents. Data analysis is conducted using Partial Least Square – Structural Equation Modeling (PLS-SEM), including outer model testing, inner model testing, and hypothesis testing. The findings are expected to indicate that innovative marketing strategies, service quality, and port facilities have a positive and significant effect on tourist satisfaction as well as on the increase of tourists at Benoa Port. The implications of this study provide insights for port management to enhance service quality, strengthen digital marketing strategies, and improve facilities to support the sustainable development of maritime tourism.